Pilates training for health of women in menopause and postmenopause - a literature review - Majewska, Emilia; Dądela, Bartosz; Zielonka, Kacper; Śliwa, Natalia; Janczura, Szymon; Markowski, Marcin; Jasińska, Joanna; Kawalska, Eliza; Gnitecki, Szymon; Borowski, Maciej (Quality in Sport, 2025)
Inroduction. Menopause is associated with significant physiological changes in women affecting the skeletal system, muscular function and mental health. The lower levels of estrogen leads to decreased bone mineral density, muscle weakness and an increased risk of osteoporosis. Additionally, hormonal fluctuations may elevate the risk of mental health disorders, including depression, anxiety and chronic stress. Aim of study. The aim of our study is to present the benefits of practicing Pilates training in women during menopause and after menopause. The study analyzed the impact of Pilates training on the musculoskeletal system and mental health of the women. Materials and methods. The work reviews articles published in the years 2013-2025 on Google Scholar or PubMed platforms. The keywords were used to search "menopausal women", "Pilates", "depression", "sleep disorder”, “muscles”. Conclusions. Regular Pilates training can improve muscle strength and eliminate pain. Furthermore, Pilates enhances flexibility and joint mobility, contributing to improved functional movement. Pilates is an effective method for stress reduction and mood improvement. Its regular practice is associated with increased body awareness, promoting overall well-being. As a comprehensive form of exercise, Pilates offers both physical and psychological benefits making it a valuable intervention for menopausal and postmenopausal women.